# Math

1. Solve the equation. -6g = 42

a. g = 7
b. g = -7
c. g = 252
d. g = -252

2. Solve the equation. x/8 = 16

a. x = 128
b. x = 24
c. x = 8
d. x = 2

3. Solve the equation. 12m = 14.4

a. m = 120
b. m = 12
c. m = 1.2
d. m = 0.12

4. Solve the equation. x/3 = -15

a. x = 45
b. x = -45
c. x = 3
d. x = -3

5. Select all of the equations that have a solution of 4. (choose only 2)

a. 5x = 20

b. 8x = -32

c. -4x = 16

d. x/2 = 2

e. x/4 = 16

1. 👍 0
2. 👎 0
3. 👁 91
1. I don't understand any of this which is why I didn't pick answers for you guys to check.

1. 👍 0
2. 👎 0
posted by Malasia
2. You just have to remember that dividing a number by itself gives a quotient of 1. When it says "solve for x" that means you want to find the value of x all by itself.

SO, if you have

-6g = 42

You just need to divide by the -6 to get g all by itself. Since -6g = 42,

-6g/-6 = 42/-6
(-6/-6)g = -7
g = -7

Then you can check your answer by multiplying by -6 to make sure you get the same original values:

-6g = -6(-7) = 42.

#2 is the same, but instead of dividing, you multiply to get rid of the fraction

x/8 = 16
(x/8)*8 = 16*8
x(8/8) = 128
x = 128

#3 and 4 are just the same, using different numbers.

For #5, just replace every x with a 4 and see whether the statement is true.

5x=20
5(4) = 20
20 = 20
so, yes. x=4 is a solution to that equation.

1. 👍 0
2. 👎 0
posted by Steve

## Similar Questions

1. ### ALGEBRA 1!PLZ HELP!

Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve the first equation for y. y = 2x-5 Substitute that for y in the second equation and solve for x. Then use the value of x to substitute back

asked by SANDRO! on November 6, 2006
2. ### Algebra

I have some problems that I am having trouble with and I have some that need checking please. Thanks! Solve the equation. 4. (x+7/4)=2(x-1/6) Find all the value(s) of x that make thedenominator(s) zero. Then solve the equation. 6.

asked by Soly on August 21, 2007
3. ### MATH

I NEED TO SOLVE FOR Y AND X im getting rele confused on this. ok here is the prob. x+y=5 x-2y=-4 equation 1 x+y=5 equation 2 x-2y=-4 Multiply equation 1 by -1. Add equation 1 to equation 2. The x term cancels. Solve for y. THEN,

asked by Tony on December 17, 2006
4. ### Math

Solve the system by addition or substitution. 3x – 4y = 8 6x – 2y = 10 Please get me on the correct track for 3x -4y =8 x=4, y=1 for 6x - 2y =10 x= 2, y= 1 Solve one equation for x. 3x = 4y + 8 x = (4y + 8)/3 Insert that value

asked by Amanda on May 20, 2007
5. ### Algebra 1

What is an equation of a line perpendicular to the line with equation y = 1 - 3x a.y=-3x + 5 b. y=3x + 5 c.y=-1/3x + 5 d. y=1/3x + 5 To solve the linear system below, which substitution of unkowns is proper ? x + 4y= -6 5x - 3y =

asked by Ley on April 22, 2013
6. ### math

determine the equation of the line in y=mx+b form that passes through 1. (-8,1) & (-9, 2) 2. (3,7) & (-5, 9) 3, (-4,0) & (4,6) Part B ) For each equation Rewreite the y=mx+b equation in general form Ax+by+c=0 where A is positive b

asked by thomas on February 8, 2007
7. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get

asked by Svetlana on October 17, 2006
8. ### math

I need help with these three problems. They are on a Study Guide and I need some refreshing up of how to do them. 17. Solve the equation using the zero product property... -8n(5n+3) 19. Solve the equation by factoring 5z^2-2z-3=0

asked by Amy on May 26, 2009
9. ### Math

I need help with these three problems. They are on a Study Guide and I need some refreshing up of how to do them. 17. Solve the equation using the zero product property... -8n(5n+3) 19. Solve the equation by factoring 5z^2-2z-3=0

asked by Amy on May 26, 2009
10. ### Math

I need help with these three problems. They are on a Study Guide and I need some refreshing up of how to do them. 17. Solve the equation using the zero product property... -8n(5n+3) 19. Solve the equation by factoring 5z^2-2z-3=0

asked by Amy on May 27, 2009

More Similar Questions